I. Kant e G. W. F. Hegel e a história da filosofia como um sistema de razão - Lara, Eduardo Garcia (2016)
The present dissertation aims to analyze the relationship between “Science” and the “History of Philosophy” in Immanuel Kant and Georg Wilhelm Friedrich Hegel from the reading, respectively, of the chapters on the “History of Pure Reason” (A852-856/B880- 884) and on the “Architectonic of Pure Reason” (A832-B860/A851-B879) in the first Critique, and the Introduction of 1823-1827/1828 to the “Lectures on the History of Philosophy”. The questions guiding the dissertation are “how Kant's and Hegel's systems, although oriented towards a systematic conception of science, allow an extrinsic intervention of the historical condition of Philosophy?” and “how such historical condition affects the constitution of scientific theories?”. Although Kant provides it with a regulative function and Hegel gives it, instead, a constitutive character, it will be attempted to show that, despite fundamental differences, both authors agree that the study of the History of Philosophy must display a systematic orientation that considers it as a development towards a scientific understanding of the discipline. According to such perspective, philosophical systems exhibit the development of reason through which it grasps its organizational scheme and the History of Philosophy is, therefore, a latent totality governed by the tension between the architectonics inherent to reason and its particular stage of manifestation. It is also argued that the answers these two authors provided to the problem of the scientific foundation of the study of the history of philosophy when developing their propaedeutic efforts to this discipline feature specific functions regarding the way they characterize the scientific enterprise. To put it another way, it is about understanding how a systematic theory of rationality can make possible an articulated vision of history as an intrinsic dimension of reason itself in the light of the externality of the empirical historical process. From the issue of the apparent relationship of mutual exclusion between the invariance, or eternity, of logical truth and the constitutive mutability of time, it will be possible to find a theoretical and conceptual framework during German idealism that allows analyzing the mode those two philosophers understand rationality and the foundations of philosophy.